Effects of acute tiagabine administration on aggressive responses of adult male parolees - Lieving, Lori M; Cherek, Don R; Lane, Scott D; Tcheremissine, Oleg V; Nouvion, Sylvain O (Journal of psychopharmacology (Oxford), 2008)
Experimental and clinical studies have supported a relationship between gamma-aminobutyric acid (GABA) and aggressive behavior in non-humans and humans. Tiagabine is a GABA uptake inhibitor that has been shown to produce acute behavioral effects in animals. In addition, tiagabine has been shown to decrease aggression in agitated patients when administered chronically. The present study was designed to investigate the effects of acute administration of tiagabine on aggressive responding on a laboratory task in adult humans. Ten adult males participated in experimental sessions on the Point Subtraction Aggression Paradigm (PSAP), which provided subjects with aggressive, escape, and monetary-reinforced response options. All subjects received four acute oral doses of Tiagabine (4, 8, 12 and 16 mg) separated by placebo sessions. Tiagabine decreased aggression at doses that either did not affect, or affected to a lesser extent, monetary-reinforced responding. The results are consistent with some prior research using the PSAP showing a possible unique role for GABA in the regulation of human aggression. A possible behavioral mechanism for the rate-decreasing effects on aggressive responding produced in the present study is that tiagabine may modify aggressive responding by suppressing reactions to aversive stimuli.